(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
Corruption poses a significant threat to the moral fabric of societies and can have a profound impact on family relationships. This scientific article explores the intersection of combating corruption with national values and family dynamics. By examining the role of ethical principles, cultural norms, and familial influences in anti-corruption efforts, this article aims to shed light on how promoting integrity and transparency can strengthen both societal values and family cohesion. Strategies for aligning anti-corruption initiatives with national values and fostering a culture of integrity within families are discussed to create a more ethical and accountable society.